INVESTIGATING THE ROLE OF KNOWLEDGE MANAGEMENT AS A TOOL FOR ENHANCING INNOVATION AND CREATIVITY IN ORGANIZATIONS - Shateri, Mahboubeh; Safari, Roya; Hozhabrnejad, Noosha; ShateriBaghiabadi, Hamid (International Journal of Research -GRANTHAALAYAH, 2016)
According to modern management literature in the fields of innovation and creativity, it is vital for organizations to innovate to keep up with increasing competition, consumer demands and emerging market fields. Here is where the role of knowledge management is highlighted as a potential key competitive advantage. This paper brings together knowledge from various areas to show that innovation is a form of organizational advantage which can be obtained by appropriate knowledge management. Focus is made the role of knowledge management in sustaining and enhancing creativity in organizations. The simulation of creativity and the allocation of resources for creative thinking methods for employees are also of vital importance. Thus, in the current corporate world, the utilization of knowledge management as a tool for enhancing creativity and innovation will present a competitive edge for organizations.